"Sheer Madness" or "Railway Politics" Iranian Style? – The Controversy over Railway Development Priorities Within the Persian Government in 1919–1920 and British Railway Imperialism. Issue 1 (2nd January 2017) - Bast, Oliver
ABSTRACT: Using Iranian and British primary sources, this essay studies the heated dispute over Iran's immediate priorities in railway building that erupted within the Iranian government in the autumn of 1919, at which moment in time making a serious start with the development of Iran's so far virtually non-existent rail infrastructure involving, first and foremost, though not necessarily exclusively, Britain, appeared to be imminent due to the related stipulations of the Anglo-Persian treaty that had been signed in August of that year. Seeking conceptual inspiration from Ronald E. Robinson's thought on Railway Imperialism and drawing on seminal work on the issue of railway building ambitions in nineteenth- and early twentieth-century Iran by Paul Luft, this analysis seeks to contribute to two separate areas of inquiry. One the one hand, it represents an intriguing case study for a (yet to be written) history of how Iranians made foreign policy during the early constitutional period (as opposed to histories of Iran's place in the foreign policies of the Great Powers during that time). On the other hand, it aims at contributing to the study of the impact of European Imperialism on the Middle East in the immediate aftermath of the First World War.